Comparing the Social Images of Youth In and Out of Residential Care. (25th April 2016) - Vaz Garrido, Margarida; Nunes Patrício, Joana; Calheiros, Maria Manuela; Lopes, Diniz
Abstract: The literature indicates that youths in residential care have been associated with negative social images. However, there have been few studies focused on these social images, specifically, comparing them with the images of youths in normative contexts. To address this issue, we conducted two studies comparing the social images people have about youths in residential care to those they hold about youths living out of care. Both studies were conducted in Portugal: Study 1 explores these images through an open‐ended questionnaire; Study 2 examines these images with a quantitative instrument. Overall, the results indicate that the perception about youths in residential care was more negative than the perception about youths out of care. Additionally, the first study probed the effect of socioeconomic status of the youths on the social images held about them and the second examined the role of the respondents' professional contact with youth in care population on these social images. The implications of the social images people have about youth in residential care for the research and intervention towards the wellbeing of this population are discussed. Copyright © 2016 John Wiley & Sons, Ltd.